Experimental study on the competition between carbon dioxide hydrate and ice below the freezing point. (15th March 2023) - Li, Yan; Maria Gambelli, Alberto; Chen, Jiangzhi; Yin, Zhenyuan; Rossi, Federico; Tronconi, Enrico; Mei, Shenghua
Graphical abstract: Highlights: Revealed the completion behavior between CO2 hydrate and ice by experiments carried out at both micrometer-scale and mesoscale. The morphological characteristics of the co-formation of ice and CO2 hydrate were observed in-situ in optical cells. Hydrate forms preferably and replaces ice at small subcoolings; while, at large subcoolings, ice forms first and hydrate emerges subsequently as a fibrous envelope around ice crystals. Experimental results shed new light on hydrate stability cycle in permafrost caused by temperature fluctuations. Abstract: As climate change and industrial requirements intensify, the potential of CO2 hydrates for carbon storage has attracted increasing attention. However, despite continuous progress, the subzero phase behavior of the CO2 -H2 O system is not well understood and merits further research. To investigate the competing and coexisting growth mechanisms of CO2 gas hydrate and ice below the quadruple point, we conducted experiments at both the micrometer-scale and mesoscale scales. The growth morphology of hydrate and ice at large and small subcooling temperatures was observed in situ in a high-pressure optical cell, and the thermodynamic behavior of the competitive process after hydrate formation was investigated in a high-pressure reactor with sands. When hydrates and ice are formed together at small subcooling temperatures, preferential hydrate formation leads to ice dissolution or even disappearance. At large subcooling temperatures, ice forms first, and the hydrate mainly forms a fibrous envelope. A small decrease in the subzero temperature after hydrate formation partially decomposes the hydrates owing to ice formation, followed by more rapid hydrate production. This study provides a thorough and expanded understanding of the competition between ice and hydrates by connecting the evolution of crystal frameworks with the thermodynamic features of the process.